Criminal Responsibility of Child Cyber Grooming Perpetrators as a Form of Child Sexual Abuse on Social Media - Ali Johardi Wirogioto (Ridwan Institute, 2023)
Human rights are the most important part of the rule of law. Every individual must respect and uphold the human rights of other individuals regardless of age. Human rights are meant not only in the real world but also in cyberspace. The development of technology has a negative impact, namely the birth of crimes that utilize technology, one of which is sexual crimes against children, namely child cyber grooming. Method: This study uses normative juridical research type. In this study, the formulation of the problem is whether child cyber grooming is a sexual crime in the digital era. And what is the criminal liability for perpetrators of child cyber grooming? Result: Childcyber grooming is a sexual crime against children using technology. This is because in its implementation it uses things that contain elements of sexuality. Perpetrators of child cyber grooming can be charged using the Pornography Law and the ITE Law.